О распространении на юго-востоке Украины некоторых раритетных видов растений - Остапко, В.М.; Тохтарь, В.К.; Муленкова, Е.Г.; Мельникова, Н.Ю.; Назаренко, А.С.; Мовчан, Т.Ю.; Зыбенко, О.В.; Шевчук, О.М. (Промышленная ботаника, 2004)
The article presents data concerning findings of species that are new for the south-east of Ukraine, new localities of aboriginal and vanishing species revealed on their range borders and range border and disjunctive species. The floristic findings conducted are indicative of the necessity of conducting further investigations directed on revealing all the localities of rare species, which is important for forming functional zones of ecologic network.